Accessibility and agglomeration: A theoretical framework for understanding the connection between transportation modes, agglomeration benefits, and types of businesses. Issue 4 (2nd April 2019) - Credit, Kevin
Abstract: While delineating the connection between transportation accessibility and economic activity has long been a topic of interest in geography and regional science, a better understanding of the agglomerative benefits of transportation systems is vital. This paper seeks to tie the concepts of accessibility and agglomeration together by arguing that accessibility benefits ultimately stem from the agglomerative potential created by various transportation investments. This line of reasoning provides an avenue to use the economic mechanisms described in agglomeration theory to analyze the effects of specific transportation modes. To do this, the paper traces the literature on the economic impacts of transportation systems and presents a theoretical framework for understanding the connection between specific transportation modes and specific agglomeration benefits. Ultimately, specific modes have unique features that are more or less conducive to specific agglomeration benefits, to which specific types of businesses also respond. These specific connections are particularly important to understand as the development of new urban transportation modes, for example, autonomous vehicles—and their potential economic impacts—increases rapidly.